Uniaxial load testing of large-scale 3D-printed concrete wall and finite-element model analysis. (15th March 2021) - Daungwilailuk, Totsawat; Pheinsusom, Phoonsak; Pansuk, Withit
Highlights: Large-scale 3D-printed concrete walls were subjected to load tests. Two different wall patterns were used in the experiment. The strain and deflection of the walls under loading were monitored. The finite-element method was used to analyze the behavior of a wall. Abstract: The load-bearing wall is one of the most important parts of three-dimensional (3D)-printed buildings. However, there is no standard or geometry for the wall panel. Additionally, one expectation for 3D-printed buildings is an architecturally flexible design. Therefore, two patterns of large-scale wall specimens were established and tested under unconfined uniaxial loading to monitor the behavior of the walls. A flat wall with an inner truss outperformed a diamond wall with regard to the strain and deflection. Additionally, a finite-element analysis was performed.